Pendidikan Agama Kristen Menurut Martin Luther Bagi Anak yang Memiliki Orang Tua Penyandang Disabilitas Intelektual - Udin Firman Hidayat; Imelda Butarbutar (UKI Press, 2022)
Moral and spirituality for children are formed in a family through Christian religious education. Parents have a major role in Christian religious education for their children. However, according to the author's observation, it’s impossible for parents with intellectual disabilities to fulfill their duties as Christian religious education mentors in the family because of their limitations. Christian religious education for children who have parents with intellectual disabilities cannot be ignored. This study aims to explore Martin Luther's view on how the role of providing Christian religious education can be carried out for children who have parents with intellectual disabilities. By using qualitative research methods with a literature study approach or library research on primary and secondary book sources, the results obtained that Christian religious education is very important for children who have parents with intellectual disabilities. Closer family who have emotional relationship or can provide assistance even as a guide for organizing Christian religious education in the family. Likewise, the Church can cooperate with special competent institutions to provide guidance, especially for parents with intellectual disabilities in the mild category so that they can carry out Christian religious education in the family. In this way children who have parents with intellectual disabilities can feel the news of joy and lead them to grow in the faith of Christ's love. Moral and spirituality for children are formed in a family through Christian religious education. Parents have a major role in Christian religious education for their children. However, according to the author's observation, it’s impossible for parents with intellectual disabilities to fulfill their duties as Christian religious education mentors in the family because of their limitations. Christian religious education for children who have parents with intellectual disabilities cannot be ignored. This study aims to explore Martin Luther's view on how the role of providing Christian religious education can be carried out for children who have parents with intellectual disabilities. By using qualitative research methods with a literature study approach or library research on primary and secondary book sources, the results obtained that Christian religious education is very important for children who have parents with intellectual disabilities. Closer family who have emotional relationship or can provide assistance even as a guide for organizing Christian religious education in the family. Likewise, the Church can cooperate with special competent institutions to provide guidance, especially for parents with intellectual disabilities in the mild category so that they can carry out Christian religious education in the family. In this way children who have parents with intellectual disabilities can feel the news of joy and lead them to grow in the faith of Christ's love.